2023
DOI: 10.3390/jcm12072500
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Event-Related Potentials in Assessing Cognitive Functions of Adult Patients with Epilepsy of Unknown Etiology

Abstract: Background: Cognitive impairment (CI) is an important consequence of epilepsy. The aim of the study was to assess cognitive performance in patients with epilepsy, using neuropsychological tests (NT) and event-related potentials (ERPs), with regard to demographic and clinical data. Methods: The study comprised 50 patients with epilepsy of unknown etiology and 46 healthy controls. Based on the NT results, the patients were divided into subgroups with/without CI. Parameters of P300 potential were compared between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…One of the most common neurological syndromes in the world is epilepsy, which remains in third position among the diseases that affect people with old age (Hirtz et al, 2007;Werhahn 2009;Queeny et al, 2018;Dunkel et al, 2023). Its rate of increase has been observed to be high in infants and aged people (Hesdorffer et al, 2011;Jeżowska-Jurczyk et al, 2023). As stated by Gagliano et al (2018), more than 45 million people have been reported to have epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common neurological syndromes in the world is epilepsy, which remains in third position among the diseases that affect people with old age (Hirtz et al, 2007;Werhahn 2009;Queeny et al, 2018;Dunkel et al, 2023). Its rate of increase has been observed to be high in infants and aged people (Hesdorffer et al, 2011;Jeżowska-Jurczyk et al, 2023). As stated by Gagliano et al (2018), more than 45 million people have been reported to have epilepsy.…”
Section: Introductionmentioning
confidence: 99%